Microstructural characterisation of a high velocity oxy-fuel thermally sprayed Al-12wt.%Sn-1wt.%Cu alloy - Kong, Chang-Jing; Brown, Paul D.; Horlock, Andrew J.; Harris, Sam J.; McCartney, D. Graham (IOP Publishing Ltd, 2001)
High velocity oxy-fuel thermal sprayed Al-12wt.%Sn-1wt.%Cu alloy coatings have been characterised both in the as-sprayed condition and following heat treatment in air at 300C for periods up to 5 hours. The as-sprayed microstructure comprises principally nanoscale Sn-rich particles embedded in an Al-rich matrix. The Sn-particles coarsen and the alloy microhardness decreases with increasing time of heat treatment.